2020
DOI: 10.25134/ieflj.v6i2.3379
|View full text |Cite
|
Sign up to set email alerts
|

What Do People Do to Sustain a Conversation: Analysis of the Features and the Speech Function of a Casual Conversation

Abstract: Conversation Analysis (CA) has a great implication in the second or foreign language teaching and learning. This study was aimed to analyse a casual conversation, to identify what people do to sustain a conversation. The conversation, which lasted for 20 minutes and involved three speakers, was transcribed verbatim. Several features of the spoken text are analysed: spontaneity, interactivity, interpersonal features, coherence features, negotiation of meaning, and speech function. The result of the analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Next, another study reported that communication strategies usage might impact learners to attain speaking proficiency and speaking self-efficacy [33]. In the course of their conversational interactions, individuals employ a variety of strategic techniques to facilitate the effective progression of discourse [34]. Thus, the two subjects, S1 and S2 have used fillers as a part of communication strategies to handle their speaking problems.…”
Section: Discussionmentioning
confidence: 99%
“…Next, another study reported that communication strategies usage might impact learners to attain speaking proficiency and speaking self-efficacy [33]. In the course of their conversational interactions, individuals employ a variety of strategic techniques to facilitate the effective progression of discourse [34]. Thus, the two subjects, S1 and S2 have used fillers as a part of communication strategies to handle their speaking problems.…”
Section: Discussionmentioning
confidence: 99%